No impact of endogenous prothrombotic conditions on the risk of central venous line‐related thrombotic events in children: results of the KIDCAT study (KIDs with Catheter Associated Thrombosis). (22nd September 2014) - Thom, K.; Male, C.; Mannhalter, C.; Quehenberger, P.; Mlczoch, E.; Luckner, D.; Marx, M.; Hanslik, A.
Summary Background and objective Central venous lines (CVLs) are the major exogenous risk factor for deep venous thrombosis (DVT) in children. The study objective was to assess whether endogenous prothrombotic conditions contribute to the risk of CVL‐related DVT in children. Methods This was a cohort study of consecutive children with heart disease requiring CVLs for perioperative care. CVLs were inserted percutaneously in the upper venous system and patients received prophylaxis with continuous unfractionated heparin (50 u kg−1 d−1). Blood samples to test for prothrombotic conditions were collected prospectively and assayed in a blinded fashion. Outcome assessment was by screening for DVT by venography, venous ultrasound and echocardiography. Results The study population consisted of 90 children, median age 2.7 years (0 months–18 years). Prevalence rates of antithrombin deficiency, protein C deficiency, protein S deficiency, heterozygous factor V Leiden, prothrombin G20210A mutation, methylentetrahydrofolate C677TT genotype, hyperhomocysteinemia, lupus anticoagulant, anticardiolipin antibodies and increased levels of lipoprotein (a) were within the range reported for the general population. At least one prothrombotic condition was present in 38% of children and combined abnormalities in 8%. The incidence of DVT was 28% (25/90), and most DVTs were asymptomatic. None of the prothrombotic conditions showed a significant association with DVT. The population attributable risk (i.e. the risk of DVT in the overall population attributable to a specific condition) did not exceed 2.2%. Conclusion Prothrombotic conditions did not have an important impact on the risk of DVT in children with short‐term CVLs. The results of the study suggest that screening for prothrombotic conditions is not justified in this setting.